Penerapan Teknologi 3D SketchUp dan Enscape Pada Desain Gereja Katolik Allah Mahamurah - Priscilla, Shareen; Adi Pratama B, A. Bayu (MDP Student Conference, 2025)
Catholic church design must harmoniously combine sacred tradition, functionality, and aesthetics, but achieving this balance is often a challenge. One of the obstacles is the difficulty of integrating design elements effectively. This study examines the use of SketchUp and Enscape in architectural planning. SketchUp, as a 3D modeling tool, helps designers create detailed representations, overcoming the limitations of visualization in traditional methods. Meanwhile, Enscape with real-time rendering capabilities improves design realism through more accurate lighting and materials. The purpose of this research is to integrate the two software in church design, in order to improve accuracy and help aesthetic and functional decision-making. The method used is qualitative with a descriptive approach. The results show that 3D technology can produce realistic designs that serve as a reference for people to see church images in more detail and concretely.